Struchium Sparganophorum (L.) Kuntze (Asteraceae): A New Angiosperm Record for the Flora of Bangladesh - Uddin, Md Salah; Uddin, Shaikh Bokhtear (Bangladesh Journal of Plant Taxonomy, 2022)
Abstract not available Bangladesh J. Plant Taxon. 29(2): 431-435, 2022 (December)